Information System for Elderly Care Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
An academic articles about information system for elderly care management in Thai supply chain aim to present elderly care management through a supply chain applying for better effective elderly care management The elderly care management needs to be appropriate to changes of globalized economy and society. The processes consisted of Suppliers, Agencies, Satisfaction and service, Customers ,All component connect with information communication technology in the Thailand with the supply chain. This truly added the society in Thailand .The supply chain and information system may be applied in the elderly care to support the tasks.